2021
DOI: 10.1111/geb.13343
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric responses of terrestrial C:N:P stoichiometry to precipitation change

Abstract: Aim The aim was to test whether the responses of C:N:P stoichiometry in plant–soil–microorganism systems to precipitation changes support the prediction of the double asymmetry model, which predicts ecological processes (i.e. aboveground productivity, soil microbial community, and soil respiration) are more sensitive to increased precipitation (R+) than decreased precipitation (R−) under normal precipitation changes, whereas more sensitive to R− than R+ under extreme precipitation changes. Location Global. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 79 publications
5
9
0
Order By: Relevance
“…Importantly, we demonstrated P addition effects on C:N:P stoichiometry of plants, soils, and microbial biomass increased with P application rates and experimental duration (Figures 3 and 4). The results agreed with the pattern observed for the global change–ecological stoichiometry relationship observed for terrestrial ecosystems (Sun, Liao, et al, 2020; Sun, Wang, et al, 2020; Sun et al, 2021; Wang et al, 2021). It is because P limitation in the terrestrial ecosystem is aggravated over time (Peñuelas et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, we demonstrated P addition effects on C:N:P stoichiometry of plants, soils, and microbial biomass increased with P application rates and experimental duration (Figures 3 and 4). The results agreed with the pattern observed for the global change–ecological stoichiometry relationship observed for terrestrial ecosystems (Sun, Liao, et al, 2020; Sun, Wang, et al, 2020; Sun et al, 2021; Wang et al, 2021). It is because P limitation in the terrestrial ecosystem is aggravated over time (Peñuelas et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that the P addition effects on terrestrial ecosystem C:N:P stoichiometry show consistency across various ecosystems and associated climates worldwide. This agrees well with the responses of terrestrial ecosystem C:N stoichiometry toward drought (Sun, Liao, et al, 2020), N addition (Sun, Wang, et al, 2020), elevated CO 2 concentration (Wang et al, 2021), warming (Sun et al, 2022), and increased precipitation (Sun et al, 2021). Consistent with previous evidences (Peñuelas et al, 2020;Wironen et al, 2018), we found P additions decreased soil N:P ratios of croplands (Figure 5), which is likely because the manure applied is characterized by low N:P ratios (Oster et al, 2018).…”
Section: Variations In P Addition Effectssupporting
confidence: 92%
“…These results were consistent with the previous study, because plants may take up N and P in excess of growth requirements when nutrients are abundant, sustaining steady growth through periods of nutrient scarcity [50]. Similarly, the relationship between RGR and nutrient ratios was not always present for each of the marsh herbaceous plants [51]. Thus, existing relationships between leaf stoichiometry and RGR might depend on experimental approaches, and species-specific and experimental approaches should be carefully considered when using the theoretical association of tree growth rate with leaf stoichiometry.…”
Section: Relationships Between Tree Growth and Leaf Traits Were Weaker In The Field Than In The Potsupporting
confidence: 92%
“…Water availability is critical to the productivity of grassland ecosystems, so precipitation is expected to be a key driver of ecosystem processes ( Wu et al., 2011 ). Precipitation increase provides higher moisture to the soil in the plant growing area, which promotes plant growth and alters the elemental cycle in plant, roots, and soil ( Sun et al., 2021 ). Yuan & Chen (2015) found that the increased rainfall reduced plant N:P ratio and cause a shift in the type of limiting elements for plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…(2006) demonstrated that there was no significant correlation between plant leaf C and P concentrations and precipitation, which implied that it was difficult to detect the response of plant C:P ratio to short-term precipitation changes. Precipitation increase promoted plant growth, resulting in more C input to the soil from litter and roots ( Zhang and Xi, 2021 ), and promoted soil N leaching ( Chen et al., 2016 ), leading to an increase in soil C:N ratio ( Sun et al., 2021 ). Soil N:P ratio was greatly determined by nutrient uptake of plant ( Abbasi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%